O semianel e o semimódulo de valores de uma curva reduzida - Emilio de Carvalho (2017)
In this work we introduce the concepts of semiring and semimodule of values of a reduced algebroid curve Q. We prove that these objects are always finitely generated and we present algorithms to obtain sets we call Standard Bases and whose values are generators for the semiring and the semimodule of values. In the analytical plane case, our results allow us to connect directly the results of Zariski and Waldi that characterize the topological type of Q and determine the set of values of the module of deferentials of Kähler, an important analytical invariant of Q